Meningkatkan Hasil Belajar Siswa Kelas II Sekolah Dasar dalam Menghitung Hasil Kali Dua Bilangan Menggunakan Benda Konkret Batangan Korek Api - Reni Septia; Narwati Narwati (Universitas Tadulako, 2022)
This research is motivated by the existence of problems, namely the low learning outcomes of students in the field of mathematics studies in calculating the product of two numbers. The purpose of this study was to identify student learning outcomes through the help of concrete matchsticks in class II SD Negeri 16 Padang Magek. The form of this research is classroom action research which consists of 2 cycles. The instrument in this study is a test of learning outcomes. The subjects of this study were students of class II SDN 16 Padang Magek, totaling 30 people. Based on the results of the study, it can be seen that in the first cycle, the average student learning outcomes were 56.33%, an increase in the second cycle, namely 83.33%. Based on the results of the research conducted, it is concluded that learning using concrete matchsticks can improve student learning outcomes.